ANALYSIS OF SELF DEVELOPMENT AND PROFESSIONALISM OF TEACHERS IN ELEMENTARY SCHOOLS - Rudi Hermansyah Sitorus; Syibrina Jihan Lubis; Dinda Widyastika (Sean Institute, 2022)
Analysis of Self Development and Professionalism of Teachers in Elementary Schools is described in this study. The purpose of the study was to determine the percentage of self development activities and teacher professionalism in elementary schools. The research was conducted by distributing questionnaires to 12 teachers in grades 1-6 from 2 different schools, then the data was analyzed and the percentage (%) of each activity was grouped into categories of ever (E), sometimes (S), and never (N). This research was conducted at SD Negeri 102126 Gunung Para, Dolok Merawan District, Serdang Bedagai Regency and students of SD Negeri 010247 Silo Lama, Silau Laut District, Asahan Regency. From the results of the study, data obtained that 41.67% had carried out self development and teacher professionalism activities, 12.50 sometimes carried out self development and professionalism activities, and 45.83% had never carried out self development and professionalism activities, one of the factors that led to the percentage of teachers who have participated in self development activities and teacher professionalism is that there are teachers who have recently served as teachers at the school.